Manual de proceso y procedimientos de comercio exterior - Ortega, Karen V. (2019)
The purpose of this research work was to prepare a Foreign Trade process and procedures manual for the Foreign Trade and Foreign Investment Observatory of the University of Otavalo, which serves as a basis for the observatory's realization together with the other processes and thus provide the advice to the inhabitants of the province of Imbabura and of the northern zone of Ecuador, in the development of inquiry so that the exporting and importing sector of the place thus have the necessary instruments and that allow them to capture the activities of their work from a more efficiently and effectively and can grow daily in your business. Within the investigation the investigation of the importance and the components of this manual has been traced, that is why it is composed of three chapters, a conceptual framework where the definitions and concepts that were of great help for knowledge and the present are detailed research work, the methodological framework where the paradigms are located, that is, where a qualitative approach was used, in addition to a field and documentary research to extract previous or historical data that serve as a base, a population and shows that they were the teachers of the University to which two were taken for an interview after being validated. The final chapter that shows the results of all the research and is in itself where the Manual of processes is carried out that will be suitable for the Observatory of Foreign Trade of the University of Otavalo.